Representasi Feminitas Tokoh Juno dalam Film Kucumbu Tubuh Indahku - Linggar Sari, Virdha Marta; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
The concept of gender is a trait that is formed and given by society to men and women, which is the result of socialization and the prevailing culture in that society. In the heteronormative view, we are bound by preconceived masculine and feminine discourses in society. This study describes the problem of how feminity is represented through the character Juno in the film Memories of My Body through a qualitative approach. The result of this study are in the form of several categories of representations of feminity according to Simone De Beauvoir on Juno’s character, besides that, it can be found messages in the film Memories of My Body which show that men with feminine characters do not always contrast with negative impressions, sometimes feminine traits in themselves men also provide comfort for others. Keywords: Feminity, Semiotics Roland Barthes, character